Korepetytor w nauczaniu domowym na ziemiach polskich doby zaborów - Nawrot-Borowska, Monika (Biuletyn Historii Wychowania, 2009)
Despite recent research on home-based education and teaching of children in the eighteenth and the nineteenth centuries, the subject of home and private tutors has yet not been properly addressed. Though there are more or less extensive mentions on the subject in question in articles devoted to home tutors or home tutelage, they do not, however, delve deeper into the investigation of the problem. Therefore, the present work attempts to characterize this position of appointed, or hired, teachers who were involved in the process of education of children in Polish families in time of partitions. The main problem is approached from the two following perspectives – the aim of the article is to: 1) indicate more precisely the status of private tutors, their social background, goals to be attained by them, their duties, responsibilities and conditions of work, i.e. a determination of their real participation in the education of children from Polish families during the time under scrutiny; and also 2) to show the contemporary standpoint expressed by the then educational columnists and journalists on the very idea of private tutoring and private tutors, as well as their postulates, recommendations to be followed and advice concerning hired teaching staff. The source material for the present analysis of the capacity and function of private tutors has been provided by relevant educational literature for professionals and parents written in the nineteenth century and the beginning of the twentieth century, professional educational periodicals and women’s and family magazines of the time. The source materials provide an excellent base for a determination of the extent and the scope of the interest of the contemporary columnists and journalists in this group of private tutors and private tutelage at the time, but also present the attitude towards the phenomenon manifested by the general public. The analysis is supplemented with additional material excerpted from contemporary memoirs and diaries that serve here as a useful illustration of the reality and practice in the actual teaching process of appointed tutors in the times of national freedom struggle in Poland.